2018
DOI: 10.4236/ojog.2018.81010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bacterial Vaginosis among Antenatal Patients at Federal Teaching Hospital Abakaliki, South East Nigeria

Abstract: Bacterial vaginosis (BV) is the most common cause of vaginal discharge in women of child bearing age. About half of these women are asymptomatic. Adverse outcomes are consistently associated with bacterial vaginosis in pregnancy and in the puerperium. This study, which was done to look at the prevalence, involved recruiting 230 participants, and screening them for BV using the Amsel's criteria. It is hoped that identification and treatment of these women will help prevent some of the sequela associated with BV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
(19 reference statements)
2
2
2
Order By: Relevance
“…The prevalence of 16.6% recorded in this study lies within the documented reported prevalence of 6%-32% from studies conducted in different regions of the world [17]. This prevalence is also consistent with figures reported from south-east and north-east Nigeria by Adinma et al [11] and Ibrahim et al [12] but higher than finding of Larrson et al [18] and lower than findings of Afolabi et al [19] and Isik et al [20].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The prevalence of 16.6% recorded in this study lies within the documented reported prevalence of 6%-32% from studies conducted in different regions of the world [17]. This prevalence is also consistent with figures reported from south-east and north-east Nigeria by Adinma et al [11] and Ibrahim et al [12] but higher than finding of Larrson et al [18] and lower than findings of Afolabi et al [19] and Isik et al [20].…”
Section: Discussionsupporting
confidence: 85%
“…Women in the age group between 25-34years had the highest prevalence of bacterial vaginosis and this was similarly reported in a study by Asiegbu et al . [17] but this differs from the age groups reported from studies by Adinma et al . [11], Ibrahim et al .…”
Section: Discussioncontrasting
confidence: 70%
“…Then, we found a prevalence of BV of 20.3%. The prevalence observed in our study is within the prevalence range (6%-32%) documented by most studies in Africa [1,20]. Indeed, prevalences of 14.2% and 30.3% have been reported in Nigeria and Zimbabwe respectively [11].…”
Section: Discussionsupporting
confidence: 84%
“…There is a highly significant association between T. vaginalis IR and the clinical sign of vaginal secretions (ᵪ 2 =49.105, p<0.001). This finding is in agreement with Asiegbu et al (2018) and does not agree with Ranjit et al (2018), who found the highest IR was with light secretion.…”
Section: Resultscontrasting
confidence: 61%